2018
DOI: 10.1093/cid/ciy558
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Treponemal Tests for the Diagnosis of Syphilis

Abstract: Treponemal immunoassays demonstrated excellent sensitivity for secondary, early latent, and seropositive primary syphilis. Sensitivity of FTA-ABS in primary syphilis was poor compared to the immunoassays and TP-PA. Given its high specificity and superior sensitivity, TP-PA is a better test to adjudicate discordant results with the reverse sequence algorithm than the FTA-ABS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 19 publications
4
64
0
3
Order By: Relevance
“…Una limitación de este estudio fue el uso del método FTA-Abs como segundo ensayo treponémico, debido a su menor sensibilidad para los estadios primario y latente tardío (78-96%) 2,22 , en lugar de la prueba TPPA recomendada por el CDC y las guías actuales del Ministerio de Salud de Argentina 23 . La FTA-Abs ha sido considerada el estándar de oro como método confirmatorio 9 , debido a su adecuada especificidad y en cada caso se realizó por personal del laboratorio entrenado y con experiencia en técnicas de inmunofluorescencia indirecta.…”
Section: Discussionunclassified
“…Una limitación de este estudio fue el uso del método FTA-Abs como segundo ensayo treponémico, debido a su menor sensibilidad para los estadios primario y latente tardío (78-96%) 2,22 , en lugar de la prueba TPPA recomendada por el CDC y las guías actuales del Ministerio de Salud de Argentina 23 . La FTA-Abs ha sido considerada el estándar de oro como método confirmatorio 9 , debido a su adecuada especificidad y en cada caso se realizó por personal del laboratorio entrenado y con experiencia en técnicas de inmunofluorescencia indirecta.…”
Section: Discussionunclassified
“…Aufgrund der Möglichkeit zur automatisierten Durchführung kommen zunehmend polyvalente ELISA-und chemolumineszenzbasierte Tests als Suchtests zum Einsatz. Alle genannten Verfahren haben eine nahezu 100 % ige Sensitivität [12], allerdings erfolgt eine Serokonversion frühestens 2-3 Wochen nach Erregerkontakt. Bei dringendem klinischem Verdacht auf eine frische Infektion muss ggf.…”
Section: Serologieunclassified
“…Our institution has been using the BioPlex IgG screen for our syphilis screening assay based its automation, high throughput, and ease of use. However, other syphilis screening assays are available, such as the Lumipulse G TP‐N chemiluminescent immunoassay, TrepSure EIA, and LIASON CIA, that detect both a treponemal IgM antibody in addition to an IgG antibody. Since the IgG BioPlex screening does not detect IgM treponemal, very early cases of syphilis may not be detected.…”
Section: Introductionmentioning
confidence: 99%
“…5 A number of studies have demonstrated a high percentage of falsely reactive tests using EIA/CLIA methods in the reverse syphilis screening algorithm. 3,[5][6][7] Reverse algorithm screening often results in a higher false-reactivity rate than traditional testing does in areas with both a low and high prevalence of syphilis. 3,5 In our previous study of the BioPlex IgG screen, the overall false-reactive rate was 1.0%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation